Hedonic vs Environmental Quality: Which Policy Can Help in Lowering Pollution Emissions? - Andrea Mantovani; Cecilia Vergari (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2013)
In this paper we compare two policy instruments that can be adopted to curb carbon emissions. The first is a conventional pollution tax. The second is an environmental campaign aiming to influence consumers to switch to a green good. We consider two different scenarios. When consumers are characterized by hedonic quality preferences, in this case the pollution tax is more efficient than the campaign. On the contrary, when consumers develop environmental quality preferences, there are cases in which the campaign is preferred. To sum up, while both policy instruments are effective in reducing pollution emissions, their efficiency viewed from a welfare perspective crucially depends on consumers' environmental awareness.
Keywords: D62; L13; 330